Earth-mapping : artists reshaping landscape - Casey, Edward S., 1939- (University of Minnesota Press ; University Presses Marketing [distributor], 2005)
Edward Casey describes the ways in which artists of the past half century have incorporated ingenious mapping techniques into their artworks. Casey follows Robert Smithson's legacy in the works of Sandy Gellis, Margot McLean, and Michelle Stuart. He also explores the visions of the earth found in the abstract paintings of Richard Diebenkorn, Jasper Johns, Willem de Kooning, Eve Ingalls, and Dan Rice.